The impact of nail psoriasis on disease activity, quality of life, and clinical variables in patients with psoriatic arthritis: A cross-sectional multicenter study - ACER KASMAN, SEVTAP; DURUÖZ, MEHMET TUNCAY (My University, 2022)
Aim Nail involvement is common in psoriatic arthritis. This study assesses clinical characteristics, nail psoriasis prevalence, and impact of nail psoriasis on disease activity in patients with psoriatic arthritis (PsA). Method This cross-sectional multicenter study was conducted by the Turkish League Against Rheumatism using PsA patients recruited from 25 centers. Demographic and clinical characteristics of PsA patients, such as disease activity measures, quality of life, and nail involvement findings were assessed during routine follow-up examinations. Patients were divided into two groups according to the presence or absence of nail psoriasis and compared using the chi(2) test or Fisher exact test for categorical variables and the t-test or Mann-Whitney U test for continuous variables. Results In 1122 individuals with PsA, 645 (57.5%) displayed nail psoriasis. The most frequent features of fingernails were ridges (38%), followed by pitting (21%) and onycholysis (19%). More females were present in both groups (with and without nail psoriasis; 64% vs 67%, P < 0.282). Patients with nail psoriasis were older, indicated more pain and fatigue, experienced greater swelling, tender joint counts, and skin disease severity, and had a higher disease activity score compared with those without nail psoriasis (all P < 0.05). Conclusion We demonstrate an increased prevalence of nail psoriasis observed in patients with psoriatic arthritis. Patients with nail involvement experience increased disease activity, lower quality of life, and diminished mental and physical status compared with those without nail involvement.
Keywords: Tıp; Dahili Tıp Bilimleri; İç Hastalıkları; İmmünoloji ve Romatoloji; Sağlık Bilimleri; Medicine; Internal Medicine Sciences; Internal Diseases; Immunology and Rheumatology; Health Sciences; ROMATOLOJİ; Klinik Tıp; Klinik Tıp (MED); RHEUMATOLOGY; CLINICAL MEDICINE; Clinical Medicine (MED); Romatoloji; Rheumatology; clinical characteristics; disease activity; nail involvement; nail psoriasis; psoriatic arthritis; quality of life; DISTAL INTERPHALANGEAL JOINT; ANKYLOSING-SPONDYLITIS; SEVERITY INDEX; INVOLVEMENT; EPIDEMIOLOGY; PATHOGENESIS; PREVALENCE; FEATURES; RECOMMENDATIONS; ONYCHOLYSIS; clinical characteristics; disease activity; nail involvement; nail psoriasis; psoriatic arthritis; quality of life